Productivity and efficiency of automotive companies in the Czech Republic: a DEA approach - Franek, Jiří; Svoboda, Ondřej (Vysoká škola báňská-Technická univerzita Ostrava, 2019)
Current issues of the Czech automotive manufacturing resonate among several topics including EU emission legislation, development of alter-native fuels and propulsion, support of R&D, preparation for the up-coming trends like autonomous cars and renewal of vehicles. Automo-tive industry is viewed as an engine of the Czech industry. The produc-tion is close to 1.5 million vehicles per year making up about 1200 bil-lion CZK in revenues. This industry consist of many companies that are interlinked in a supplier network. The goal of this paper is to investigate efficiency of automotive companies in the Czech Republic and to com-pare regions and identify those with relative low efficiency. To achieve this, we employed data envelopment analysis (DEA) which is a non-parametric approach to measure efficiency of a finite number of deci-sion-making units (DMUs). This approach is very sensitive to the choice of measures. We applied a selecting model, which could also help to identify the optimal number of inputs and outputs from a group that make economic sense. Using selected inputs and outputs, we performed analysis of efficiency with CCR and BCC models. Results suggest rela-tively concentrated efficiency with large differences among automotive firms across NUTS2 regions.
Produktivita a efektivita automobilových společností v České republice: přístup DEA
Keywords: data envelopment analysis; efficiency; productivity; automotive industry; inputs; outputs; analýza datových obalů; účinnost; produktivita; automobilový průmysl; vstupy; výstupy